Mucins as a factor of carcinogenesis and a potential target for therapy of mucinous ovarian tumors - A. G. Kedrova; T. A. Greyan (Опухоли женской репродуктивной системы)
Mucinous ovarian carcinoma is a rare histological form of epithelial ovarian cancer. These tumors demonstrate poor objective response to standard chemotherapy regimens for epithelial ovarian cancer and PARP inhibitors maintenance therapy, resulting in short overall and disease-free survival, as well as a poor prognosis in patients with advanced disease. Macroscopically, mucinous ovarian carcinoma is characterized by the presence of mucus in the cystic cavity, consisting mainly of mucin. This review examines in detail the role of mucins in the pathogenesis and therapy of mucinous ovarian carcinoma in the context of the formation of chemoresistance and a possible point for targeted therapy.